Effect of superabsorbent polymer introduction on properties of alkali-activated slag mortar. (18th July 2022) - Yang, Zhengxian; Shi, Peng; Zhang, Yong; Li, Zhenming
Highlights: The effects of SAP introduction on different properties of AAS are studied. Different dosages and mixing ways (dry mixing and wet mixing) are considered. SAP addition can improve the strength and impermeability of AAS mortar. The frost resistance becomes better when more SAP is introduced regardless of the mixing way. Abstract: Internal curing by superabsorbent polymer (SAP) has been applied in alkali-activated slag (AAS) systems by a few previous studies with the purpose to mitigate the autogenous shrinkage. However, the effects of SAP on other properties of AAS have been rarely studied. In this paper, the workability, strength, permeability, and frost resistance of AAS mortar with synthesized SAP are investigated besides the autogenous shrinkage. Two SAP introducing ways (dry mixing and wet mixing) are considered. It is found that the flowability of AAS mortar decreases with the increase of SAP dosage regardless of the introducing way. The strength and permeability increase with the SAP dosage when it is below a certain amount depending on the mixing way. The autogenous shrinkage can be mitigated significantly by the incorporation of SAP and the mitigating effect is more pronounced by wet mixing. The frost resistance becomes better when more SAP is introduced in either way. The mechanisms behind these phenomena are explained based on the characterization results on the reaction kinetics, reaction products and pore structure of the mixtures with SAP.